2012
DOI: 10.1017/s0022029912000301
|View full text |Cite
|
Sign up to set email alerts
|

Protein degradation in bovine milk caused byStreptococcus agalactiae

Abstract: Streptococcus (Str.) agalactiae is a contagious mastitis bacterium, often associated with cases of subclinical mastitis. Different mastitis bacteria have been evaluated previously from a diagnostic point of view, but there is a lack of knowledge concerning their effect on milk composition. Protein composition is important in achieving optimal yield and texture when milk is processed to fermented products, such as cheese and yoghurt, and is thus of great economic value. The aim of this in vitro study was to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
0
13
0
10
Order By: Relevance
“…These results and the results obtained in the present study differ in relation to the correlation between SCC and fat (r = 0.2217) and are similar in relation to SCC and protein (r = 0.2346). The increased content of milk protein that occurred in high SCC milk can be explained by the change in milk composition in response to inflammation in the mammary gland, and consequently the increase in concentration of serum proteins in milk (ÅKERSTEDT et al, 2012). Machado et al (2000) reported that milk from tanks with SCC > 1,500,000 cells/mL presented higher content of fat than milk from herds with SCC < 1,000,000 cells/mL, and herds with SCC < 500,000 cells/mL presented higher content of protein than herds with SCC > 500,000 cells/mL.…”
Section: Correlation Between Composition and Hygiene Indicators Of Bumentioning
confidence: 99%
See 1 more Smart Citation
“…These results and the results obtained in the present study differ in relation to the correlation between SCC and fat (r = 0.2217) and are similar in relation to SCC and protein (r = 0.2346). The increased content of milk protein that occurred in high SCC milk can be explained by the change in milk composition in response to inflammation in the mammary gland, and consequently the increase in concentration of serum proteins in milk (ÅKERSTEDT et al, 2012). Machado et al (2000) reported that milk from tanks with SCC > 1,500,000 cells/mL presented higher content of fat than milk from herds with SCC < 1,000,000 cells/mL, and herds with SCC < 500,000 cells/mL presented higher content of protein than herds with SCC > 500,000 cells/mL.…”
Section: Correlation Between Composition and Hygiene Indicators Of Bumentioning
confidence: 99%
“…Due to the increase of somatic cell count (SCC) of milk in response to intramammary infection, milk quality is reduced because of changes in milk composition, such as increased concentration of free fatty acids and serum proteins, decreased casein and lactose content, and changes in milk mineral contents (ÅKERSTEDT et al, 2012). These changes occur in response to the action of inflammation mediators and the activity of enzymes and toxins synthetized by mastitis pathogens (BRANDT et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Estas perdas são devidas principalmente ao menor rendimento de fabricação de derivados lácteos pela alteração na composição do leite e pela menor vida de prateleira do leite e seus derivados (ÅKERSTEDT et al, 2012;ARCHER et al, 2013). Para o produtor de leite, as perdas se devem à redução da produção e ao descarte do leite, ao trabalho extra para tratamento e custo de aplicação de antibióticos e ao aumento do risco de doenças subsequentes, além de ser uma das principais causas de descarte de vacas em rebanhos leiteiros (GROENENDAAL et al, 2004;HOGEVEEN et al, 2011).…”
Section: Mastite Bovinaunclassified
“…Nos casos de mastite, as principais alterações no leite são a elevação da quantidade de ácidos graxos livres, a diminuição do teor de caseína do leite e aumento do teor de proteínas do soro (ÅKERSTEDT et al, 2012), assim como redução da concentração de lactose, alteração de teores de sódio, cloro, potássio e cálcio e aumento do pH. Estas alterações são causadas pelos mediadores químicos da inflamação e pela atividade das enzimas e toxinas bacterianas no leite e podem ocorrer em diferentes intensidades dependendo da forma de manifestação e duração da inflamação da glândula mamária (BRANDT et al, 2010).…”
Section: Mastite Bovinaunclassified
See 1 more Smart Citation